Factors Impeding the Learning of English as a Second Language among Male Students in Public Sector Colleges at the Intermediate Level? - Shahid, Choudhry; Jatoi, Zahid Ali; Gurmani, Muhammad Taimoor; Saif, Laiba (Pakistan Journal of Humanities and Social Sciences, 2023)
The primary aim of the study is to investigate the English language learning at intermediate level in the Province of Punjab, Pakistan. To achieve the objective of the study situational analysis and literature review approach for substantive theorizing and historical interpretation is adopted as suggested by Karl Popper. Teachers and students of numerous social surroundings who teach and study in the public and private sector colleges in the province of Punjab have reported numerous problems, in the published articles from 2015 to 2022, they face in learning English language. In the teaching and learning contexts Urdu and regional languages have been reported widely used in the previous studies, and other main reasons highlighted through the review of the literature which are impeding the learners in second language learning include; crowded classrooms, less motivation, literature, teacher-centered teaching, indifferent teacher attitude, inadequate teacher training, and ineffective Syllabus. This study has recommended with teachers' training support, implementing interactive teaching methods, and using the target language in the classes by motivating the learners, these hurdles can be overcome easily.